2013
DOI: 10.1124/dmd.113.053983
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Infection Alters the Expression of Hepatobiliary and Placental Drug Transporters in Pregnant Mice

Abstract: Preventing and treating malaria in pregnancy is a global health priority. However little is known regarding the impact of malaria infection on the maternal and fetal disposition of pharmaceuticals and other xenobiotics. Our objective was to characterize expression of key determinants of drug-disposition in maternal and fetal tissues in a validated murine model of experimental placental malaria. Balb/c mice were infected with Plasmodium berghei at mid gestation [gestational day (GD) 13] and maternal, placental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 55 publications
(56 reference statements)
4
25
1
Order By: Relevance
“…It was observed that the placental mRNA expression of Abcb1a, Abcb1b, Abcc1, Abcc2, Abcc3, and Abcg2 were significantly downregulated in the mice group with malaria infection as compared to the control group. In addition, the Mdr1 protein expression was also decreased in the malaria infected group compared to control (302). …”
Section: Recent Findings From Studies Involving Multiple Abc Transmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the placental mRNA expression of Abcb1a, Abcb1b, Abcc1, Abcc2, Abcc3, and Abcg2 were significantly downregulated in the mice group with malaria infection as compared to the control group. In addition, the Mdr1 protein expression was also decreased in the malaria infected group compared to control (302). …”
Section: Recent Findings From Studies Involving Multiple Abc Transmentioning
confidence: 99%
“…While saquinavir is also a substrate for MRP1, despite the fact that MRP1 levels are higher at late gestation, saquinavir showed increased placental transport probably because of the basolateral localization (300). Cressman et al (302) studied the impact of malaria infection on the expression of placental ABC transporters in pregnant mice. It was observed that the placental mRNA expression of Abcb1a, Abcb1b, Abcc1, Abcc2, Abcc3, and Abcg2 were significantly downregulated in the mice group with malaria infection as compared to the control group.…”
Section: Recent Findings From Studies Involving Multiple Abc Transmentioning
confidence: 99%
“…Emerging evidence has demonstrated that expression and function of drug transporters are modulated by inflammation [2530]. Liver, intestine, kidney, blood-brain barrier and placenta are the main studied tissues and the modulation of transporter activity has been connected to the activity of proinflammatory cytokines, including IL1, IL6 and TNFα [29].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes have been observed previously during MiP; for example, malaria has been shown to alter placental expression of SLC amino acid and glucose transporters, ultimately preventing sufficient foetal access to these substrates and potentially contributing foetal growth restriction . Additionally, using the Plasmodium berghei ANKA (PbA) murine model of MiP, we previously observed a downregulation in the expression of the ABC drug transporters Mdr1a, Mdr1b, Mrp1‐3 and Bcrp in the placenta of malaria‐infected animals . Furthermore, ABC and SLC transporters located in other tissues such as the liver and kidney play an important role in the absorption, distribution and elimination of drugs.…”
Section: Introductionmentioning
confidence: 99%